Insecticidal effect of several essential oils against Musca domestica - Klauck V.* (2018)
© 2017, Springer-Verlag London Ltd.This study aimed to evaluate for the first time the insecticidal effects of essential oils of bergamot (Citrus bergamia), palmarosa grass (Cymbopogon martini), vetiver grass (Vetiveria zizanioides), and red cedar (Juniperus virginiana) against the house fly (Musca domestica). The in vitro study was performed in captured adult flies, which were separated on testing cages (n = 20). Subsequently, the essential oils cited above were used in the concentrations of 1, 5, and 10%, and a control group was maintained for test validation. All flies were monitored for 8 h after treatment. All four oils showed insecticidal effect against the fly species studied in vitro and after 8 h of treatment, an efficacy of 73% was observed for the essential oil of bergamot, 55% for palmarosa grass, 75% for vetiver grass, and 89% for red cedar. We conclude that the essential oils tested showed insecticidal effect against house fly, acting as an environmentally sustainable alternative to be applied in human habitats, especially against flies’ resistant to chemical insecticides. In addition, the use of such oils may decrease the doses of synthetic drugs routinely used.